Compliance of a baby-friendly designated hospital in Ghana with the WHO/UNICEF baby and mother-friendly care practices: $hFaith Agbozo, Doris Ocansey, Prosper Atitto, and Albrecht Jahn - Agbozo, Faith; Ocansey, Doris; Atitto, Prosper; Jahn, Albrecht (Journal of human lactation, 2020)
Although the Baby-Friendly Hospital Initiative has improved breastfeeding rates globally, weak monitoring still affects hospital-level implementation. Research aim: To reassess compliance of a Baby-Friendly Hospital with the Ten Steps to Successful Breastfeeding, International Code of Marketing of Breast-milk Substitutes, HIV and Infant Feeding, and Mother-Friendly Care following the WHO/UNICEF global criteria.
First published May 21, 2019
Gesehen am 06.03.2020